1984
DOI: 10.1002/mus.880070405
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of scoliosis in duchenne muscular dystrophy

Abstract: There are not, as yet, clear indications for the surgical management of scoliosis in Duchenne muscular dystrophy (DMD), taking into account the varying severity of the clinical course. Monitoring the vital capacity can be most important for the indication and timing of surgery. In some cases, delaying surgical intervention with conservative management using spinal braces and wheelchair inserts can permit the restrictive lung syndrome to advance to the point that surgery will be contraindicated. Ten such patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 12 publications
1
47
0
3
Order By: Relevance
“…There has been much debate about the indications and timing of surgery in DMD but there is now a general concurrence that spinal deformity correction should be undertaken prior to onset of cardio-respiratory compromise [3,4]. There have been suggestions that surgery should be undertaken if the Cobb angle is between 20 and 50° [5][6][7]. Early operation has been shown to improve outcome in long term follow up studies [3,4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…There has been much debate about the indications and timing of surgery in DMD but there is now a general concurrence that spinal deformity correction should be undertaken prior to onset of cardio-respiratory compromise [3,4]. There have been suggestions that surgery should be undertaken if the Cobb angle is between 20 and 50° [5][6][7]. Early operation has been shown to improve outcome in long term follow up studies [3,4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It is the most common of the dystrophies (1 in 5000 live male births) and is characterised by a progressive muscle wasting and weakness leading to a loss of ambulation by the early teens. Muscle weakness is due to lack of the protein dystrophin in skeletal muscle cell membranes, and this can be tested for by immunohistochemical techniques or by western blotting electrophoresis on a muscle biopsy specimen [3,7,9,10,13,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…According to many authors, spinal fusion has no effects on the natural involution of the respiratory function [5, 33,35,36,47], both at short-term and at a 5-year follow-up [38]. In contrast, Rideau et al [44] and Galasko et al [17] reported a period of VC stabilisation in surgically treated patients of 24 and 36 months, respectively (Fig. 3).…”
Section: Introductionmentioning
confidence: 97%
“…Rideau et al [44] classified patients with DMD into three groups by their VC. They asserted that VC increases until the age of 10-12 years, until a plateau is reached; then it progressively decreases over the following years (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation